Family meals and the well‐being of adolescents. Issue 11 (31st October 2013) - Utter, Jennifer; Denny, Simon; Robinson, Elizabeth; Fleming, Theresa; Ameratunga, Shanthi; Grant, Sue
<x xml:space="preserve">Abstract</x> Aim The current study describes the relationships between family meals and family connectedness, parental monitoring and parent–child communication and determines if frequent family meals are associated with better mental well‐being and fewer risktaking behaviours among adolescents. Methods Data were collected as part of Youth'07, a nationally representative survey of the health and well‐being of secondary school students in New Zealand (n = 9107). Results Frequent family meals were positively associated with better indicators of family relationships (P < 0.001). Likewise, frequent family meals were significantly associated with higher well‐being scores (P < 0.001), lower depression scores (P < 0.001) and fewer risk‐taking behaviours (P < 0.001), even after controlling for age, sex, ethnicity, deprivation, family connectedness, parental monitoring and parental communication. Conclusions Our findings suggest that family meals may provide a unique opportunity for building stronger families and young people. Creating environments where frequent family meals are normative, valued and feasible for families may result in benefits for young people that extend beyond good nutrition.